2022
DOI: 10.3390/biomedicines10112965
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the IFN-Pathway by Human Papillomavirus Proteins: Antiviral Immune Response Evasion Mechanism

Abstract: A persistent infection with the so-called high-risk Human Papillomaviruses (hr-HPVs) plays a fundamental role in the development of different neoplasms. The expression of the HPV proteins throughout the different steps of the viral life cycle produce a disruption of several cellular processes, including immune response, which can lead to cell transformation. The interferon-mediated response plays an important role in eliminating HPV-infected and -transformed cells. The ability of HPV to disrupt the proper func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…The determinants of HR-HPV persistent infections are not precise. Still, they may be related to the inability of the host to mount an adequate innate immune response and a robust cell-mediated immunity, as well as the ability of the viral proteins to evade immune detection ( 20 22 ). Although only 0.6% of HPV infections are known to progress to cancer, a 16-year follow-up study has shown that the risk of developing cancer is 75.4 times higher in women with persistent HR-HPV infections compared to HPV-negative women ( 23 ).…”
Section: Cervical Cancer Pathogenesismentioning
confidence: 99%

Molecular aspects of cervical cancer: a pathogenesis update

Vallejo-Ruiz,
Gutiérrez-Xicotencatl,
Medina-Contreras
et al. 2024
Front. Oncol.
Self Cite
“…The determinants of HR-HPV persistent infections are not precise. Still, they may be related to the inability of the host to mount an adequate innate immune response and a robust cell-mediated immunity, as well as the ability of the viral proteins to evade immune detection ( 20 22 ). Although only 0.6% of HPV infections are known to progress to cancer, a 16-year follow-up study has shown that the risk of developing cancer is 75.4 times higher in women with persistent HR-HPV infections compared to HPV-negative women ( 23 ).…”
Section: Cervical Cancer Pathogenesismentioning
confidence: 99%

Molecular aspects of cervical cancer: a pathogenesis update

Vallejo-Ruiz,
Gutiérrez-Xicotencatl,
Medina-Contreras
et al. 2024
Front. Oncol.
Self Cite
“…For instance, chemically derived Imiquimod is an immunomodulatory dosage that affects both the innate and adaptive immune responses and the activation of natural killer cells, the production and release of interferon (IFN)-alpha, tumor necrosis factor-alpha, and interleukin-12, in addition to the suppression of viral replication. 240 Cidofovir is another nucleotide analogue that works by inhibiting viral DNA polymerase, and the medication cidofovir also helps to reduce the HPV-positive tumor cells' propensity for metastasis. 241 Other chemically derived antivirals, such as Ganciclovir, Acyclovir, and Famciclovir, target the viral DNA of the Epstein−Bar virus during the infection stage, thus preventing its progression along with the inhibition of host cell DNA polymerase (Figure 4).…”
Section: Antiviral Strategiesmentioning
confidence: 99%
“…Next, the potential of human papillomavirus to interfere with the proper functioning of the interferon response based on several molecular pathways coordinated by human papillomavirus proteins aimed to prevent infection clearance results in the creation of an immunotolerant environment that promotes the establishment of persistence and cancer. For instance, chemically derived Imiquimod is an immunomodulatory dosage that affects both the innate and adaptive immune responses and the activation of natural killer cells, the production and release of interferon (IFN)-alpha, tumor necrosis factor-alpha, and interleukin-12, in addition to the suppression of viral replication . Cidofovir is another nucleotide analogue that works by inhibiting viral DNA polymerase, and the medication cidofovir also helps to reduce the HPV-positive tumor cells’ propensity for metastasis .…”
Section: Antiviral Strategiesmentioning
confidence: 99%
“…E6 also contributes to the downregulation of the immune response against HPV by suppressing IFR3 (Interferon Regulatory Factor 3), a transcription factor for interferons (IFNs) ( 132 , 133 ), and by inhibiting IFNA (interferon alpha) interaction with its receptor ( 134 ). E7 acts synergically by inhibiting TLR9/CD289 (Toll-like receptor-9), present intracellularly in several immune cell types ( 135 , 136 ).…”
Section: Hpv Viral Components and Molecular Genetic And Epigenetic Me...mentioning
confidence: 99%